Вероятностные модели процессов обслуживания вызовов и управления ими в информационных сетях следующего поколения - Бидный, Ю. М. (ХНУРЭ, 2011)
The given work is connected with research in the field of probabilistic models for service call processes and its management in information next generation networks. For their in this report are used probabilistic models such as control Markov’s circuit in discrete time observation and semiMarkov’s processes in continuous time observation. It is considered realization this models for the basic call management processes in intelligent network.
Keywords: системы управления вызовами; обслуживание вызовов